LITTLE-KNOWN PAGES OF THE BIOGRAPHY OF F.I. GOREPEKIN - Albogacieva, Makka Sultan-Gireevna (History, Archeology and Ethnography of the Caucasus, 2022)
The article provides little-known details from the life of the researcher of writing systems, folklore and ethnography of the Ingush people – Foma Ivanovich Gorepekin. Based on the available sources, documents of archival fonds and materials of the Gorepekin family archive, the author attempts to clarify some gaps in his biography: origin, exact dates of life and death, information about awards and “exposures”, etc. The author has already carried out work on collecting material and publishing articles, as well as a published a facsimile of his works in 2006. However, there have been no other studies of F.I. Gorepekin’s scientific work in Russian historiography, which explains the relevance of our study. The newly discovered facts provide an opportunity to dispel some myths related to his life path and his academic interests. Some of the materials included in this article are first introduced into scientific circulation and shed light on many little-known pages of the researcher’s life. We pay special attention to issues related to his scientific research and negative assessments by academician N.Ya. Marr and his colleagues. During this period, the theory of N. Ya. Marr was strong, and in this context, the work of a little-known Caucasian scholar from Vladikavkaz caused only annoyance and irritation. The works of F.I. Gorepekin were not given due attention by the staff of the Japhetic Institute, to whom they were sent for expert assessment. Analysis of the material allows us to conclude about the reasons for their claims and negative assessment of his works . The introduction of original details about F.I. Gorepekin allows us to see how politics and power could ruin the fates of researchers, regardless of their real contribution to science. The biography of Foma Ivanovich provides a balanced characterization of that period through the fate of one individual. During the study, the method of biographical research was applied.
Keywords: F.I. Gorepekin; N.Ya. Marr; history; ethnography; archaeology; local history; Caucasus; Ingush; Chechens